2015
DOI: 10.11648/j.jfns.s.2015030102.42
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Irradiation Treatment in Eliminating E. coli O157:H7 and Salmonella in Dried Organic Herb Samples Intended for Use in Blended Tea

Abstract: Abstract:Blended tea with different herbs, seeds and dehydrated vegetable substances bring a world of flavours, aromas and colours to tea. Tea is usually made with dried tea leaves, or blended with other dried herbs and pouring boiling water over the leaves and letting them stay for a few minutes and then sip. This study was done to evaluate the microbial contamination of dried organic lemongrass, mint and jasmine samples intended to prepare flavoured tea and also to see the effect of gamma irradiation in inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Coliform bacteria were detected in 20 % of samples [ 9 ]. However, generic E. coli and pathogenic E.coli 0157:H7 were detected in dried tea samples [ 31 ]. Anosike and Oranusi (2018) [ 32 ] also reported that bacterial counts ranged from 1.7 × 10 2 to 4.5 × 10 2 cfu/g in tea samples collected from the Nigerian retail market.…”
Section: Resultsmentioning
confidence: 99%
“…Coliform bacteria were detected in 20 % of samples [ 9 ]. However, generic E. coli and pathogenic E.coli 0157:H7 were detected in dried tea samples [ 31 ]. Anosike and Oranusi (2018) [ 32 ] also reported that bacterial counts ranged from 1.7 × 10 2 to 4.5 × 10 2 cfu/g in tea samples collected from the Nigerian retail market.…”
Section: Resultsmentioning
confidence: 99%
“…The total fecal coliform levels present in each sample were determined based on the method described by Zaman, Alam, Mortuza, and Bari (2015). Briefly, approximately 1 g of each sample was homogenized in 225 mL of an enterobacteria enriched broth-Mossel pre-enrichment medium (Oxoid Ltd, Hampshire, England) followed by incubation at 35 C for 24 h. Then, 1 mL of pre-enriched cultures were mixed with 9 mL of 2X Escherichia coli (E. coli) medium (Nissui Co. Ltd., Tokyo, Japan) followed by incubation at 35 C for 24 h. To confirm the presence of fecal coliform, one loop of the culture was inoculated in 10 mL of 1X (E. coli) medium with a Durham fermentation tube followed by incubation for 20 h at 42 C. The production of gas in the tube confirms the presence of fecal coliform.…”
Section: Total Fecal Coliform Countmentioning
confidence: 99%